Guidelines for Promoting Organizational Commitment of Personnel in Textile Industry in Sam Phran District, Nakhon Pathom Province. - Narathong, Nuchkamol; Phongsitkanchana, Thongchai; Rittiboonchai, Wisit (Journal of Management Science Nakhon Pathom Rajabhat University, 2018)
The objectives of the research were to: 1) study 8 happiness indexes and organizational commitment of personnel in textile industry; 2) compare organizational commitment of personnel as classified by personal factors; 3) study 8 happiness indexes affecting organizational commitment of personnel; and identify guidelines for promoting organizational commitment of personnel. The sample was 278 personnel in textile industry in Sam Phran District, Nakhon Pathom Province, derived by simple random sampling from drawing lots, and 3 interviewees derived by purposive sampling. The research instruments were a questionnaire and an interview form constructed by the researcher. Descriptive statistics used for data analysis were percentage, mean and standard deviation, and inferential statistics used were t-test, one-way analysis of variance, least significant difference, correlation coefficient, stepwise multiple regression and content analysis. The findings of this research were as follows: 1. Overall the 8 happiness indexes of personnel in textile industry was at a high level, while the organizational commitment was at a high level. 2. The personnel with differences in work tenure and income had different level of organizational commitment with a statistical significance level of .05. However, there was no difference with those classified by gender and position. 3. The 8 happiness indexes had positive relation with organizational commitment with a statistical significance level of .01. Moreover, the happiness indexes in the aspects of happy society, happy brain, happy money and happy heart affected personnel’s organizational commitment at the percentage of 43. 4. Guidelines for promoting organizational commitment were reducing conflicts; building labor relations; placing importance in giving equal benefits to all employees; providing knowledge through monthly training; listening to personnel’s opinions; reminding personnel about relaxation, exercise and healthcare; and constructing good environment in workplace. Article history : Accepted 7 September 2014 SIMILARITY INDEX = 0.00